1978
DOI: 10.1002/clc.4960010104
|View full text |Cite
|
Sign up to set email alerts
|

The ischemic segment and left ventricular function during exercise angina

Abstract: Summary: Improvement of the quality of transpulmonary left ventriculograms by exercise was demonstrated in 5 patients in a pre-study. In the main study transpulmonary left ventriculography was performed in 10 patients with coronary artery disease (CAD) at rest and during exercise, producing maximum angina pectoris (AP). Left ventricular pressure was recorded simultaneously. The extent of CAD, demonstrated in all patients by coronary angiography, was quantitated by a score. In the exercise ventriculograms, loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
1988
1988

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Left ventricular cine-angiography during exercise has demonstrated that areas of myocardium, which develop wall motion abnormalities correlate well with coronary artery narrowings (Sharma et al 1975, Rentrop et al 1978. With this in mind, the early Echo report of Fogelman et al (1972) of wall motion abnormalities during angi-na has started a growing interest in exercise echocardiography.…”
Section: Echocardiography and Wall Motion During Exercisementioning
confidence: 99%
“…Left ventricular cine-angiography during exercise has demonstrated that areas of myocardium, which develop wall motion abnormalities correlate well with coronary artery narrowings (Sharma et al 1975, Rentrop et al 1978. With this in mind, the early Echo report of Fogelman et al (1972) of wall motion abnormalities during angi-na has started a growing interest in exercise echocardiography.…”
Section: Echocardiography and Wall Motion During Exercisementioning
confidence: 99%
“…187 In addition to diagnosing the presence of CHD, qUllntitative assessment of segmental wall motion at known levels of stress may allow assessment of severity of coronary artery stenosis. Quantification of wall motion abnormalities with exercise has been described by Sharmtl and Taylor (91) using left contrast ventriculography, and recently has been improved by Rentrop et al (80), using transpulmonary left contrast ventriculograms. These authors showed a significant correlation between the extent of exercise induced segmental wall motion abnormality and extent and severity of CHD.…”
Section: Diicaulonmentioning
confidence: 99%